Peak power reduction and workload balancing by space-time multiplexing based demand-supply matching for 3D thousand-core microprocessor - P. D., Sai Manoj (2013)
Space-time multiplexing is utilized for demand-supply matching between many-core microprocessors and power converters. Adaptive clustering is developed to classify cores by similar power level in space and similar power behavior in time. In each power management cycle, minimum number of power converters are allocated for space-time multiplexed matching, which is physically enabled by 3D through-silicon-vias. Moreover, demand-response based task adjustment is applied to reduce peak power and to balance workload. The proposed power management system is verified by system models with physical design parameters and benched power traces, which show 38.10% peak power reduction and 2.60x balanced workload.